Relationship of Adiponectin and High-Sensitivity C-Reactive Protein with Left Ventricular Dysfunction among Patients Undergoing Coronary Angiography - Mohammed S. Al-Hakimi (University of Science and Technology, Sana’a, Yemen, 2023)
Background: Decreased levels of adiponectin (APN) and elevated levels of high-sensitivity C-reactive protein (hs-CRP) have been found as predictors of left ventricular dysfunction and cardiovascular events. Therefore, this study aimed to assess the relationship of APN and hs-CRP with the severity of left ventricular dysfunction among Egyptian patients undergoing coronary angiography (CAG). Methods: A cross-sectional study was conducted among 100 Egyptian patients who underwent clinically indicated CAG at Suez Canal University Hospital in Ismailia - Egypt, from May 2009 to December 2010. The left ventricular ejection fraction (LVEF) scoring system was used to assess left ventricular function based on echocardiographic findings. Pearson correlation was used to determine the relationship of APN and hs-CRP levels with echocardiographic LVEF score, and analysis of variance (ANOVA) was used to compare clinical and biochemical parameters among patients according to left ventricular function at P-value <0.05. Results: The mean hs-CRP level had a significant weak negative correlation with the mean HDL-cholesterol level (r = -0.222; P = 0.048), while the mean APN level had a significant weak negative correlation with BMI (r = -0.269; P = 0.007) but a significant weak positive correlation with the mean hs-CRP level (r = 0.215; P = 0.031) and a significant moderate positive correlation with the mean HDL-cholesterol level (r = 0.302; P = 0.002). Left ventricular function in patients undergoing CAG was normal in 34 (34%), mildly impaired in 41 (41%) patients and moderately impaired in 25 (25%), with significantly different mean hs-CRP levels among the three groups (P = 0.025) that increased from normal to moderately impaired left ventricular function. However, there was no statistically significant difference in left ventricular function according to the mean level of APN. Conclusion: The hs-CRP level is negatively correlated with HDL-cholesterol, while APN is negatively correlated with BMI and hs-CRP but positively correlated with HDL-cholesterol in Egyptian patients undergoing CAG. The hs- CRP level correlates with the severity of left ventricular dysfunction. However, left ventricular function does not appear to correlate with APN levels.